Consensus document on coding of cardiac magnetic resonance examinations in Portugal - Ferreira, MA (2012)
One of the obstacles to more frequent and appropriate use of cardiac magnetic resonance (CMR) in Portugal has been the lack of specific codes that accurately describe these examinations as they are currently performed. In this consensus document, recommendations are made for updating and standardizing CMR codes in Portugal. Guidance on which techniques and codes should be used in the most common clinical scenarios is also provided.